TRANSFER INFORMASI INTRA-INDUSTRI DI SEKITAR PENGUMUMAN PERUBAHAN DIVIDEN: Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) 2002-2004 - Widiatmoko, J. (Jurnal Ilmiah Telaah Manajemen, 2007)
The aim of this research is to prove the existance of intra industry information transfer which happen in dividend chabge announcemen by a firm that influence stock price of other firm in the same industry subsector. The population of this research incude all of manufactur firms that list in Indonesia Stock Exchange during 2002-2004. Using purposive sampling method, obtained 15 firms that report dividend decrease and 15 firms that report dividend increase. From 15 reporter firms, there are 112 non reporter firms dividend decrease and 119 non reporter firms dividend increase. The results of this research show that intra industry transfer information only happen in h +4 and h +5 for dividend increase announcement. In h -4, there is contagion effect mean that dividend decrease regarded as sign that there is performance decrease in reporter firm that contaminates to non-reporter firms in dividend increase announcement. Only happened in h -5 information transfer in the same sector and happen competitive effect. Meanwhile, decrease and increase dividend announcement not influence to cummulative abnormal return. Key words: divident announcement, transfer of information, contagion effect, competitive effect, cummulative abnormal return.